The role of zoledronic acid in the treatment of malignancies - Wawrocka-Pawlak, Marlena; Z. Pawlak, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2003)
Bone metastases and hypercalcemia are the most common skeletal or skeletal-related manifestations of malignancy. Because increased bone turnover plays a central role in destruction of bone by metastatic lesions, bisphosphonates, as the inhibitors of osteoclast activity, are being assessed in attempts to ameliorate skeletal complications and inhibit the growth of bone metastases. Zoledronic acid is a potent, third generation, nitrogen-containing bisphosphonate. In the preclinical setting, zoledronic acid has demonstrated superior potency regarding inhibition of osteolysis and reduction of hypercalcemia as compared with other bisphosphonates. Zoledronic acid has also demonstrated direct anti-tumor activity. The high potency of zoledronic acid has been demonstrated clinically. Zoledronic acid was superior to pamidronate in normalizing serum calcium in patients with tumor-induced hypercalcemia. Zoledronic acid is at least as effective as pamidronate in treatment of osteolytic metastases. However, zoledronic acid is the first bisphosphonate to reduce skeletal complications in patients with bone metastases from prostate and renal cancer, as well as non-small cell lung cancer. Thus, based on preclinical assays and clinical data, zoledronic acid is now poised to become the mew standard of treatment for tumor-induced hypercalcemia and metastatic bone disease.